An Investigation of the Effects of Low Concentrations of Chlorpyrifos on Epididymal Sperm Mutation in Rats - De Silva, W.A.J.P.; Deepananda, K.H.M.A.; Chandana, E.P.S.; Priyanganie, P.M.C.; Peiris, L.D.C.; Samayawardhena, L.A. (Sri Lanka Association for the Advancement of Science, Colombo, 2001)
Attached.